Frescoes in the Baths of Qasr Amra castle. The Aspects of Perception of Ancient Yeritage in the Muslim Arab culture - Petrova, Lyubava D. (Actual Problems of Theory and History of Art, 2012)
The article deals with problems of interpretation of the ancient heritage in the context of Arab-Muslim culture of Umayyad era basing on the example of desert castle Qasr Amra paintings. This monument shows a variant of perception of ancient art diff erent from that in Western Europe. It is not one of the “minor renaissances” which were typical for Western Europe and Byzantium and were essentially temporary revivals of antiquarian tastes and classicizing currents, and certainly not an analogue of Italian Renaissance, but a continued unbroken tradition beginning in antiquity.
Keywords: age of the Umayyad; monumental painting; fresco; the interpretation of ancient heritage; art of the Middle East; Desert castle; baths; palace buildings